REFLECTIVE PRACTICE AS TOOLS TO EXPLORE IN-SERVICE TEACHERS’ BELIEFS AND CLASSROOM PRACTICES: INDONESIAN EFL TEACHERS’ VOICES - Dwi Bayu Saputra; Didi Suherdi; Rojab Siti Rodliyah (JOALL (Journal of Applied Linguistics and Literature), 2020)
Reflective practice is widely acknowledged as the most effective means to create effective teacher who wants to have better understanding of their works. It has been explicitly stated in western academic teacher education curriculum due to its significant impact on constructing life-long learning for teachers. However, this beneficial contribution of teachers’ professional development is not growing within the context of English as a foreign Language (EFL) teaching. Accordingly, this descriptive qualitative research aimed at (1) investigating teachers’ beliefs in teaching and learning English by utilizing reflective tools, and (2) attempting to identify whether or not their beliefs are implemented in their practices in which the reasons will also be explored. The data were gathered through interviews and classroom observations as the main source. Three English teachers were investigated to elicit their beliefs about teaching and learning. The findings showed years of teaching experiences and past experiences as a learner are the most arisen theme in which the initial facet strongly affects the way they perceive teaching, and the latter occurrence theme indirectly shape the teachers’ beliefs. As regards to the relation of their practices and their stated belief, however, not all of their beliefs were implemented in the classroom due to several factors such as the students’ factors, time-constraint, and the school obligations.